2023
DOI: 10.1038/s41598-023-33014-4
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning reduces soft costs for residential solar photovoltaics

Abstract: Further deployment of rooftop solar photovoltaics (PV) hinges on the reduction of soft (non-hardware) costs—now larger and more resistant to reductions than hardware costs. The largest portion of these soft costs is the expenses solar companies incur to acquire new customers. In this study, we demonstrate the value of a shift from significance-based methodologies to prediction-oriented models to better identify PV adopters and reduce soft costs. We employ machine learning to predict PV adopters and non-adopter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“… 73 These electronic devices convert sunlight into electrical energy through the photovoltaic effect, generating electricity when sunlight interacts with the cell’s materials and causes the expulsion of electrons. 74 The basic building block of a solar cell is a p-n junction, which allows for the generation of electricity when sunlight interacts with the cell’s materials. 75 Solar cell technology has evolved to utilize p-n junctions in photovoltaic solar cells, which consist of p- and n-type semiconductors coupled with a p-n junction to produce electric current.…”
Section: Solar Cellmentioning
confidence: 99%
“… 73 These electronic devices convert sunlight into electrical energy through the photovoltaic effect, generating electricity when sunlight interacts with the cell’s materials and causes the expulsion of electrons. 74 The basic building block of a solar cell is a p-n junction, which allows for the generation of electricity when sunlight interacts with the cell’s materials. 75 Solar cell technology has evolved to utilize p-n junctions in photovoltaic solar cells, which consist of p- and n-type semiconductors coupled with a p-n junction to produce electric current.…”
Section: Solar Cellmentioning
confidence: 99%
“…Teng Zhong et al [29] showed the potential of city-scale rooftops, which reduce the labor cost through deep learning with the proposed spatial optimization sampling strategy. Dong's [30] research showed that machine learning can reduce customer acquisition costs by 15% (USD 0.07/Watt), and they identified new market opportunities for solar companies to expand and diversify their customer bases. Soft costs and customer acquisition costs are notoriously difficult to reduce due to the challenges in predicting forthcoming events.…”
Section: Economic Analysis and Impacts On Societymentioning
confidence: 99%
“…As more consumers select rooftops for PV installation, companies require data and tools to predict solar irradiation [7]. However, accurately predicting solar irradiation becomes crucial with the growing use of rooftop PV installations [8]. By 2030, building-integrated PV in EU member states is projected to surpass 22% of Europe's annual power consumption [1,9].…”
Section: Introductionmentioning
confidence: 99%